Case report: a 33 years-old alcoholic male with diarrhea and progressive muscle weakness mimicking Guillain-Barré syndrome - Rudolph, Anja; Doubrovinskaia, Sofia; Knabbe, Johannes; Seliger, Corinna; Lenhard, Thorsten (Frontiers in neurology, 2023)
BackgroundA subacute manifestation of muscle weakness in temporal association with a diarrheal intestinal infection is always suspicious of Guillain-Barré syndrome (GBS). GBS is characterized as an acute inflammatory polyneuroradiculopathy, mediated by cross-reacting autoantibodies and typically triggered by various infections, vaccinations or other causes. Hyponatremia can be associated with GBS and is usually seen in more severe cases. However, the presence of relevant hyponatremia in a case suspicious of GBS can lead to a diagnostic dilemma. We here describe an intriguing and initially misleading case of hyponatremia mimicking GBS, where repeated and thorough electrophysiology was the key to the correct diagnosis.Case presentationA 33 years-old man with a history of severe alcohol dependence and schizophrenia developed progressive muscle weakness in the course of a preceding episode of diarrhea. Neurological examination revealed a leg-accentuated tetraplegia with global areflexia. There was also a complex oculomotor dysfunction. Laboratory tests showed hyponatremia of 110 mM. Cerebrospinal-fluid analysis showed a normal cell count and cytological evaluation, protein concentration within the normal range. Electroneurography showed severe proximal nerve conduction block as evidenced by prolonged F-wave latency and distal nerve conduction block as evidenced by prolonged distal motor latencies and reduced motor nerve conduction velocities (NCV) in all peripheral nerves examined. GBS-associated ganglioside autoantibodies were absent. After compensation of hyponatremia alone, muscle weakness improved rapidly and nerve conduction velocity improved similarly. These dynamics are not consistent with GBS and unnecessary immunoglobulin treatment could be avoided.ConclusionSuspicion of GBS in the presence of relevant hyponatremia can be misleading as hyponatremia is able to mimic GBS. We demonstrate that repeated and accurate nerve conduction studies together with F-wave diagnostics is helpful to make the correct diagnosis. We discuss the mechanisms of the causes of hyponatremia in GBS and contrast these with the electropyhsiological changes caused by hyponatremia itself. The correct diagnosis will prevent the uncritical use of intravenous immunoglobulins and save unnecessary costs. Also, a possible aggravation of the hyponatremia by immunoglobulin treatment can be averted.
Gesehen am 26.09.2023